Impact of watershed topography on hyporheic exchange. (August 2016) - Caruso, Alice; Ridolfi, Luca; Boano, Fulvio
Highlights: The impact of groundwater fluxes on hyporheic exchange is analysed at basin scale. Groundwater upwelling along the river corridor shows a strong spatial variability. The variability of groundwater flows induces a fragmentation of the hyporeic zone. Abstract: Among the interactions between surface water bodies and aquifers, hyporheic exchange has been recognized as a key process for nutrient cycling and contaminant transport. Even though hyporheic exchange is strongly controlled by groundwater discharge, our understanding of the impact of the regional groundwater flow on hyporheic fluxes is still limited because of the complexity arising from the multi-scale nature of these interactions. In this work, we investigate the role of watershed topography on river-aquifer interactions by way of a semi-analytical model, in which the landscape topography is used to approximate the groundwater head distribution. The analysis of a case study shows how the complex topographic structure is the direct cause of a substantial spatial variability of the aquifer-river exchange. Groundwater upwelling along the river corridor is estimated and its influence on the hyporheic zone is discussed. In particular, the fragmentation of the hyporeic corridor induced by groundwater discharge at the basin scale is highlighted.